Ecobrick: A Creative Solution for Plastic Waste Management in Karang Umpu Village - Hendianysah Hendianysah; M. Yasin al Arif; Alamsyah Nurrahman Putra (Smart Society, 2023)
Indonesia ranks as the second-largest producer of plastic waste in the world, with plastic taking around 1,000 years to decompose, leading to environmental pollution. One effective solution is the implementation of the 3R concept (Reduce, Reuse, Recycle) and the production of ecobricks, which can be easily done using available materials and tools. This community service project aims to raise public awareness, particularly in Karang Umpu Village, about using ecobricks to maintain environmental cleanliness and health. The method used is educational outreach, enabling the community to understand how to manage and repurpose plastic waste. The results showed an increase in public knowledge regarding the types, utilization, and management of plastic waste by 85%, compared to 53% before the outreach. With this outreach, the community is expected to be able to manage and repurpose plastic waste through the ecobrick method, preventing waste accumulation and reducing environmental pollution, thereby creating a clean and healthy environment.